A67 ANTIBODY-MEDIATED REJECTION AFTER LIVER TRANSPLANTATION: A CASE SERIES. (15th March 2019) - Vuille-Lessard, É; Bilodeau, M; Willems, B; Marleau, D; Vincent, C; Giard, J; Villeneuve, J; Soucy, G; Nguyen, B; Huard, G
Abstract: Background: Antibody-mediated rejection (AMR) is being increasingly recognized after liver transplantation (LT). Nevertheless, its diagnosis is often delayed and its management remains an area of uncertainty. Aims: Review and describe all cases of humoral rejection after liver transplantation at the Centre Hospitalier de l'Université de Montréal (CHUM). Methods: This was a case series of all adults diagnosed with AMR after LT at the CHUM in Montreal, Canada. Through a retrospective chart review, we examined the demographic characteristics of patients, the diagnostic process leading to identification of the cases, including donor specific antibodies (DSA) as well as histological findings, and the management of AMR, short and long term clinical outcomes and survival. Results: Four cases (1.9%) of AMR were identified among 211 LT between January 2015 and March 2018. Median age was 59 years and all cases were men. Baseline liver disease included one case of cirrhosis from hepatitis C, B and D, one case of NASH cirrhosis and two cases of hepatocellular carcinoma. One patient had a retransplantation for chronic rejection. Median time from LT to diagnosis of AMR was 226 days (25–1060 days). class II DSAs were present in all four patients with a median mean fluorescence intensity (MFI) of 2187 (IQR 1279–5163) and two patients had a MFI >10, 000. All 4 patients had at least one liver biopsy showing features of microvascular injury: portal endothelial cell hypertrophy (4/4 cases), microvasculitis (1/4 case), centrilobular sinusoidal disruption and congestion (2/4 cases). There was severe bile duct damage with cholestasis in all cases. Features of acute T-cell mediated rejection (TCMR) were also seen in all cases in the early stage of the disease and subsided with treatment of TCMR. Two cases had features of chronic AMR. Focal C4d endothelial staining by immunofluorescence technique were seen in 1/3 liver samples. Treatment of AMR, following a course of corticosteroids, included intravenous immunoglobulins (4/4 cases), plasmapheresis (3/4 cases) and anti-thymoglobulins (2/4 cases). Median observation time was 646 days (275–1046 days). Two patients developed complications following treatment of AMR including bacteremia, cytomegalovirus reactivation, esophageal candidiasis, pulmonary aspergillosis, disseminated cryptococcosis with meningitis and lung adenocarcinoma. One patient died from pulmonary aspergillosis. Conclusions: AMR after LT is a rare and possibly underdiagnosed condition. It should be suspected in any patients with steroid-refractory rejection, especially in the presence of class II DSA. Although potentially associated with long term infectious and malignant complications, early treatment of AMR could prevent graft loss. Funding Agencies: None